(The Planning Model for Development of Cacao Industry in Indonesia) - Agus Sudibyo; Hartrisari -; Arbainah - (Warta Industri Hasil Pertanian, 1999)
Research on planning model for development o cacao industry had been conducted and designed by using system methodology, and analytical hierarchy process. the system indentificayion consisted of constructing related input-output diagrams and strategic priorities analysis. It was found that the ystem approach was an effective tool in identifying a complicated system. Based on analytical hierarchy process the study concluded that planning of cacao industry development resulted high competitiveness product development strategic with score 0.3984 as the frist priority  and product diversification strategic with score 0.3550as secound priority. there were five selected factors that could influence the development strategic of cacao industry, i.e. technology (0.2986) capital and finance (.1568) raw cacao quality (0.1556) infra structure including facility (0.1102) and production or operation management (0.1090) meanwhile actor who had the high to small role in implement selected strategy included businessman/ frim (0.4920) goverment (0.1792) and farmer (0.1522) the study had also shown that the objective could be reached through increassing added value of commodity (0.1643) increasing market share (0.1498) increasing forein exchange (0.1466)maximum profit taking (0.1339) and increasing farner income taking (0.1320).